Penalaran dan komunikasi matematis: Tinjauan sistematis strategi efektif dalam mengembangkan kompetensi siswa - Nur Fazria Adam; Tedy Machmud; Majid Majid (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2026)
Mathematical reasoning and communication are essential competencies for students. This systematic review examines teaching strategies and methods that effectively enhance these competencies. This study employed a Systematic Literature Review  method following the PRISMA 2020 guidelines. Data were collected from the Scopus database using the keywords “Communication AND Mathematics AND Education AND Indonesia” for publications from 2016 to 2026. Of the 52 articles, 9 articles that met the inclusion criteria. This review highlights how traditional instructional approaches have evolved toward a greater emphasis on conceptual understanding and problem-solving. The main strategies discussed include Realistic Mathematics Education, Inquiry-Based Learning, collaborative learning, and technology integration. The review also explores the role of student engagement, demonstrating that active participation and intellectual involvement are key factors in developing these competencies. The findings indicate that contextual, interactive, and cognitively supported instruction is the most effective approach for fostering these competencies. The integration of reasoning and communication as interdependent competencies further emphasizes the importance of an integrated instructional approach.